The Effect of Peer-Support to Students’ Academic Stress in Boarding School with House System - Rizkita, Muhammad (Proceeding International Conference on Science and Engineering, 2020)
The purpose of this research is to describe the level of academic stress and peer-support among students; in boarding school with house system; and to analyze the role of peer-support to students’ academic stress in boarding school with house system. Peer-support is measured by Child and Adolescent Social Support Scale-Academic (CASSS-A) with Cronbach ? =. 97 (Sonia, 2014) as an independent variable and academic stress is measured by Educational Stress Scale for Adolescents (ESSA) with Cronbach ? =.82 (Sun, 2012) as a dependent variable. Data collection was carried out at SMAN Sumatera Selatan as one one of boarding school that implements a house system in Indonesia with 60 out of 300 students as a sample in this research. Researchers use a cluster sampling technique. The result of this research shows that peer-support is on an average level; academic stress is on an average level that analyze by descriptive analysis technique. Simple linear analysis techniques are used as inferential analysis which shows that there is no effect of peer-support to students’ academic stress in a boarding school with house system, in other words, Ha in this research is accepted. As the researcher evaluated the result of this research, self-efficacy found as a mediator variable between social support (peer support, parent support, and teacher support) to students’ academic stress in a boarding school with house system and become a recommendation for upcoming research.